Perancangan dan Implementasi Server Presensi Online dengan Geotagging berbasis Foto - Mohammad Rizky Dwisaputra; Primantara Hari Trisnawan; Reza Andria Siregar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Today, governments or any office attendance system still uses paper or RFID (Radio Frequency Identification) and finger prints in their office, and if someone needs to work outside the office, it will be difficult to maintain and monitor their employee. Therefore, the writer suggests an attendance system with their selfie picture based on their location. Because everyone nowadays uses their smartphone for communication, implementing this attendance system is the best solution, as the employee begins by logging in with their credentials, uploading a selfie photo with geotagging, and displaying their time and location. The server that maintains their data must be checked, and testing the network performance from outside the office using either a cellular network or fixed broadband from the employee side started with filling out their credentials to upload their picture, which contains geolocation, and showing up their time and location for monitoring.